The global incidence rate of type 2 diabetes related chronic kidney disease and predictions by Bayesian age-period-cohort analysis: findings from the Global Burden of Disease Study 2019 - Yu, Junpu; Luo, Fanhui; Zhang, Yiwen; Yang, Jingli; Yu, Shuxia; Li, Nan; Yang, Aimin; Ma, Li; Li, Jinsheng (Frontiers in Endocrinology, 2025)
AimsTo evaluate the spatial-temporal changes in the incidence of type 2 diabetes related chronic kidney disease (CKD-T2DM) from 1990 to 2019, categorized by age and sex in 21 regions with different socio-demographic indexes (SDI), and to predict the incidence rate between 2020 and 2030.MethodsData on the burden of CKD-T2DM were obtained from the Global Burden of Disease Study 2019. Age-standardized incidence rates (ASIR) were estimated by sex, age, region, SDI, and specifically in China. The trends of ASIR were assessed using Joinpoint model to calculate the average annual percentage changes (AAPCs) and their 95% confidence intervals. Prediction was conducted using the Bayesian age-period-cohort (BAPC) model.ResultIn 2019, the ASIR of global CKD-T2DM increased with age in both sexes, and was highest in the older 75 age group. The ASIR of CKD-T2DM in males was higher than those in females. Overall, the global ASIR of CKD-T2DM increased from 1990 to 2019 in both sexes and all age groups. The most significant increase was observed in the 15–49 age group [males: AAPC=1.42, 95%CI:(1.35-1.49); females: AAPC=1.18,95%CI:(1.13-1.23)]. Besides, the upward trends in ASIR of CKD-T2DM were observed in most SDI regions and GBD regions. The changing trends in ASIR of CKD-T2DM in China were similar to the global trends. Finally, the predicted ASIR was also found to be increased globally and also in China in both sex from 2020 to 2030.ConclusionThe global CKD-T2DM incidence rates increased from 1990 to 2019 in both sexes, most regions and in China., and also increased globally between 2020 and 2030. Therefore, it is important to input more medical resources and establish prevention strategies for the increasing trends of CKD-T2DM.